RAD51 (rs1801320) gene polymorphism and breast cancer risk in Turkish population - (:unkn) unknown (E-CENTURY PUBLISHING CORP, 2017)
Background: Breast cancer is frequently observed multifactorial disorder worldwide and in Turkey as well. The genetic factors have been found as main cause of breast cancer development and the genes responsible for DNA repair have been shown to provide maintenance of chromosomal stability. RAD51 gene plays an important role in formation of Holliday junction which is branched intermediate product that occurs during homolog recombination-based DSB repair. RAD51 (rs1801320) gene variant is supposed to change RAD51 gene expression and contribute to DNA instability and development of cancer, including breast cancer. Objectives: In the light of these data, the purpose of this study is to investigate association between RAD51 (rs1801320) variant and breast cancer risk in hospital-based Turkish population. Materials and methods: Genotyping for RAD51 (rs1801320) variant in DNA samples of 548 breast cancer patients and 360 healthy women was done by PCR-RFLP method. SPSS software was used to calculate genotype and allele frequencies, p, chi(2) and OR (95% confidence intervals) values. Finally, Hardy-Weinberg equilibrium (HWE) was confirmed for tested patient and control populations and statistical power (SP) was calculated. Conclusion: This study showed no statistically significant association between RAD51 (rs1801320) variant and breast cancer (chi(2)=0.852, P=0.653).
Keywords: Breast cancer; RAD51; rs1801320; Turkish population; REPAIR GENES; SUSCEPTIBILITY; DNA; WOMEN; 135G-GREATER-THAN-C; METAANALYSIS; VARIANTS; BRCA2